Barriers for early initiation and exclusive breastfeeding up to six months in predominantly rural Sri Lanka: a need to strengthen policy implementation - Thilini Chanchala Agampodi; Neerodha Kithmini Dharmasoma; Iresha Sandamali Koralagedara; Thushari Dissanayaka; Janith Warnasekara; Suneth Buddhika Agampodi; Rafael Perez-Escamilla (BMC, 2021)
Abstract Background Sri Lanka was named as the first-ever 'Green' breastfeeding nation status by the World Breastfeeding Trends Initiative (WBTi) in January 2020. However, improvements are still needed. This study aims to identify barriers and facilitators for early initiation of breastfeeding and exclusive breastfeeding for 6 months in rural Sri Lanka. Methods We conducted in-depth interviews with 16 mothers with infants, who had been unable to practice early initiation of breastfeeding and/or exclusive breastfeeding (EBF), in six child-welfare clinics in Anuradhapura, Sri Lanka. Three focus group discussions were held with public health midwives (PHMs). Initial thematic analysis that built upon force field and social learning theories was performed. Results Main barriers for EBF were clustered at three time periods; during the first 2-3 days, 2-3 weeks, and 4-5 months postpartum. Early barriers included cesarean section pain, poor breast latch, maternal exhaustion, suboptimal maternity ward environment, and lack of support for breastfeeding. Around 2-3 weeks postpartum mothers introduced water or infant formula due to social norms and poor support. On-demand feeding was misunderstood. Around 4 and 5 months postpartum, EBF ended due to return to work. PHMs reported a heavy workload limiting their time to support breastfeeding. Conclusion EBF interruption was due to diverse individual- and environnmental- level barriers that varied across the first 6 months. To improve EBF, Sri Lanka should focus on strengthening policies for reducing the excessive rates of cesarean section, improving support in maternity ward facilities, fostering on-demand breastfeeding, enhancing support for working mothers and reducing the work load of PHMs.